Assalamuallaikum PERBANDINGAN TOKOH DAN PENOKOHAN DALAM FILM NINJA HATTORI-KUN DAN DORAEMON KARYA FUJIKO FUJIO - Farica Farica Adhani; Ratna Dewi Kartikasari (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2022)
This study aims to compare the characters and characterizations between the Ninja Hattori-Kun film and Fujiko Fujio's Doraemon. This research is a qualitative research, while the object of the research is the film Ninja Hattori-Kun with Doraemon by Fujiko Fujio. The data in this study were obtained from character descriptions and characterizations from the two films. Data analysis was carried out using a structuralism approach developed by Ferdinand de Saussure. From the results of the discussion, it can be concluded that the duration of the two Ninja Hattori-Kun films by Fujiko Fujio is 35 minutes and the duration of the Doraemon film by Fujiko Fujio is 30 minutes. In the film Ninja Hattori-Kun by Fujiko Fujio has as many as 6 characters and in the film Doraemon by Fujiko Fujio has as many as 6 characters. Both have advantages, the main character is usually designed as a person with special talents and advantages. If Doraemon has a magic bag, Ninja Hattori has ninja moves. The advantages possessed by Doraemon and Ninja Hattori are used to help lazy children. When Doraemon helps Nobita, Ninja Hattori helps Kenichi. Nobita and Kenichi are said to be lazy and weak, so they rely on the hero's abilities. Both wear glasses. From this research, there are similarities and differences in the two literary works. Keywords: qualitative, descriptive, character, characterization, animation.